Supervisee Experiences of Broadening and Narrowing in Counselling Supervision - Gazzola, Nicola; Theriault, Anne (European Journal for Qualitative Research in Psychotherapy, 2009)
This study investigated supervisee perspectives of broadening (i.e., thinking and acting creatively and being open to exploring new ways of being) and narrowing (i.e., the experience of perceiving one’s choices as limited) processes in their supervisory experiences. Ten supervisees who completed all requirements for a master’s degree in counselling were interviewed using a semi-structured interview. Data were analyzed using a variation of the consensual qualitative research method developed by Hill, Thompson, and Williams (1997). Participants described their experiences of broadening and narrowing and their perceptions of their supervisors’ contributions to these processes. The findings include four categories of broadening and five categories of narrowing, each with subcategories. Implications for the process of supervision are offered.